Challenges and opportunities in the new era of communication: digitalization and public relations - ÖZGEN, EBRU (My University, 2022)
It has been inevitable for public relations to avoid the changes in the globalizing and technologically developing world and adapt to them. Communication underlies public relations. It is one of the professions that is most heavily influenced by all the developments in communication technologies. Thus, the profession had to adapt to new communication technologies, while digitalization gradually drove selected media and target publics to evolution accordingly. This study aims to trace the impact of digitalization in public relations as a profession in Turkey. To that end, a literature review in light of technological developments in communication and information technologies is conducted. Then, academicians from the field and practitioners, who currently work with public relations agencies, are interviewed. Snowball sampling was the selected qualitative method for the research design. The study concluded that the ways in which public relations activities are conducted differ significantly from a decade ago with the development of technological tools, university curricula must be updated in accordance with such developments, and new employment opportunities must be opened up to those, who do not only possess theoretical knowledge but also technological know-how. The study attempts to shed light on the changing trends in the profession from the eyes of both practitioners and academicians in the field as well as the problems that arise from digitalization alongside suggested solutions by practitioners. It is also hoped that this study
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)